The Use of Digital Payments in Batik MSMEs at Beringharjo Market Yogyakarta - Wardani, Salsabila Arisha; Sukirno, Sukirno (Jurnal Locus Penelitian dan Pengabdian, 2025)
This study aims to (1) analyze digital payment usage's impact on Batik MSME sales, (2) identify obstacles faced by Batik MSMEs, (3) explore strategies to overcome the digital payment adoption gap, and (4) examine its effect on the accuracy and relevance of Batik MSME financial information. Employing a qualitative phenomenological approach, it explores individuals' lived experiences. Subjects are Batik MSMEs (population: 14; sample: 5 via purposive sampling). Data were gathered through participatory observation, in-depth interviews, and documentation, with validity ensured via source and method triangulation. Analysis involved data collection, reduction, and presentation. Findings show: (1) Positive sales impacts for Batik Daradasih, Batik Ana, and Batik Iis, but not for Batik Atik and Batik Anis due to limited digital literacy, location, and customer interest. (2) Poor signal hinders transactions. (3) Merchants seek government-provided Wi-Fi, POS systems, and training. (4) Improved financial information at the former three; low at the latter due to poor digital understanding.